Aroma Analysis of Table Grape Berries Based on Electronic Nose Detection - Shengyang Niu; Xuewei Liu; Meiling Lin; Xiucai Fan; Ying Zhang; Lei Sun; Chonghuai Liu; Jianfu Jiang (Agronomy)
In this study, the aroma of 182 table grapes was detected using a PEN3.5 electronic nose in order to explore the aroma components of table grape berries and provide a reference for aroma evaluation and quality improvements. Table grape varieties from the Zhengzhou Fruit Research Institute of the Chinese Academy of Agricultural Sciences were used as research materials. All of them were harvested in fruit trees over 10 years old from August to October 2023, which provided a reference for aroma evaluation and quality improvement of the table grapes. Radar analysis, correlation analysis, principal component (PCA) analysis, cluster analysis, and difference analysis were used to study these aroma substances. The results show that the sensor contribution rate from high to low is W5S (nitrogen oxides), W2S (alcohols and some aromatic compounds), W1S (alkanes), and W2W (sensor contribution rate from high to low). Cluster analysis can distinguish the varieties of table grapes a with common aroma content, and the varieties with a higher content are in the second category (II). PCA showed that the contribution rate of the first and second principal components of the three main sensors was 97.6% and 2.3%, respectively, and the total contribution value was 99.9%. The contribution rates of the first and second principal components of the three aromatic sensors are 79.5% and 15.9%, respectively, and the total contribution value is 95.4%. The results showed that there were significant differences in the content and composition of aroma substances in different grape varieties. Eight special germplasm with strong aroma (organic compounds of nitrogen oxides, alcohols, alkanes and sulfur) were selected: ‘Spabang’, ‘Neijingxiang’, ‘Zaotian Muscat’, ‘Jinmeigui’, ‘Zhengguo 6’, ‘Muscat Angel’, ‘Zizao’, and ‘Qiumi’. This study confirmed that electronic nose technology can effectively distinguish different varieties of table grapes. This study not only provides a scientific basis for the variety selection for the table grape processing industry, but it can also be used for male or female grape hybridization, which provides valuable data resources for table grape breeding.